Endophytic Fusarium solani: A rich source of cytotoxic and antimicrobial napthaquinone and aza-anthraquinone derivatives. (2018) - Khan, Nasima; Afroz, Farhana; Begum, Mst. Nadira; Roy Rony, Satyajit; Sharmin, Suriya; Moni, Fatema; Mahmood Hasan, Choudhury; Shaha, Koushik; Sohrab, Md. Hossain
Graphical abstract: Highlights: Endophytric fungi are natural reservoir for bioactive secondary metabolites. Fusarium solani, an endophytic fungus, is a rich source for secondary metabolites specially for quinone groups. Napthaquinone and aza-anthraquinone derivatives have significant antimicrobial, antioxidant and cytotoxic effect. Napthaquinone and aza-anthraquinone derivatives have the potentiality to be lead for anticancer and antimicrobial agent. Aza-anthraquinone derivatives are more bioactive than napthaquinone group due to the presence of nitrogen group. Abstract: This study reports the chemical investigation and bioactivity of the secondary metabolites produced by the endophytic fungus Fusarium solani isolated from Cassia alata Linn. growing in Bangladesh. This plant was collected from conservation forest in Bangladesh and belongs to the Caesalpiniaceae family. The endophytic fungus Fusarium solani was isolated from the tissue of root of this plant. The fungal strain was identified by morphological characters and DNA sequencing. The crude organic extract of the fungal strain was proven to be active when tested for cytotoxicity against Brine Shrimp Lethality Bioassay, antimicrobial and antioxidant activity. The bioactivity guided fractionation of the ethyl acetate extract leads to the isolation of seven secondary metabolites in pure form. The structures of the isolated compounds were determined by the analysis of NMR and mass spectroscopic data. Bioassay investigation of the isolated secondary metabolites suggested aza-anthraquinones are more potent bioactive compounds as anticancer and antimicrobial agent.